2012
DOI: 10.1123/jsr.21.4.354
|View full text |Cite
|
Sign up to set email alerts
|

Scapular Kinematics and Subacromial-Impingement Syndrome: A Meta-Analysis

Abstract: Context:The literature does not present a consistent pattern of altered scapular kinematics in patients with shoulder-impingement syndrome (SIS). Objectives: To perform meta-analyses of published comparative studies to determine the consistent differences in scapular kinematics between subjects with SIS and controls. In addition, the purpose was to analyze factors of the data-collection methods to explain the inconsistencies in reported kinematics. The results of this study will help guide future research and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(88 citation statements)
references
References 45 publications
2
82
0
2
Order By: Relevance
“…Objective, quantitative measurement of scapular kinematics can provide an assessment of abnormal movement patterns associated with shoulder dysfunction 1 , such as reduced upward rotation and posterior tilt during arm elevation observed in shoulder impingement [2][3][4][5][6][7][8] . Measurement of scapular kinematics, however, is difficult due to the bone's deep position and gliding nature beneath the skin surface 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Objective, quantitative measurement of scapular kinematics can provide an assessment of abnormal movement patterns associated with shoulder dysfunction 1 , such as reduced upward rotation and posterior tilt during arm elevation observed in shoulder impingement [2][3][4][5][6][7][8] . Measurement of scapular kinematics, however, is difficult due to the bone's deep position and gliding nature beneath the skin surface 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Results indicate that for a population of adolescent athletes with an amateur sports level, the dyskinesis prevalence is high; however, it is not associated with pain and does not seem to affect measures of upper limb function. Although some studies support the relationship between pain/ lesion and scapular dyskinesis 2,[7][8][9][10][11] , more than half of the current sample (56.7%) presented changes in scapular movement without, however, being associated with shoulder pain. The results of this study corroborate those of Oliveira et al 28 who analyzed amateur male athletes with shoulder injury syndrome and observed no association between dyskinesis and shoulder pain.…”
Section: Discussionmentioning
confidence: 88%
“…Specifically, the modification in the scapula positioning, called scapular dyskinesis, has been studied because it presents possible relations with the presence of pain and shoulder injuries in athletes 2,[6][7][8] . Most of the studies state the relation between shoulder pain/ injury and scapular dyskinesis 2,7,[9][10][11] . Such research ensures that ORIGINAL ARTICLE DOI 10.5935/2595-0118.20180009 changes in scapular kinematics may result in structural and functional changes in the glenohumeral and acromioclavicular joints, decreased subacromial space, changes in the scapular muscles activation and, consequently, leading to dysfunctions such as shoulder-rotator cuff syndrome, rotator cuff tendinopathies, glenohumeral instability, and other conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Borstad & Ludewig, 2002;P.M. Ludewig & Cook, 2000;Timmons et al, 2012) and dysfunction or weakness of the rotator cuff musculature (Brox et al, 1999;N. Hanchard et al, 2004;Leroux et al, 1994;Michener et al, 2003;Reddy, Mohr, Pink, & Jobe, 2000;Sorohan & Mc Creesh, 2009;Warner, Micheli, Arslanian, Kennedy, & Kennedy, 1990).…”
Section: Introductionmentioning
confidence: 99%